Clinical outcomes of diverticular disease in young adults: results from a tertiary referral center - Santacroce, Giovanni; Lenti, Marco Vincenzo; Abruzzese, Giulia Maria; Alunno, Giacomo; Di Terlizzi, Francesco; Frenna, Carmine; Gentile, Antonella; Latorre, Mario Andrea; Petrucci, Clarissa; Ruggeri, Damiano; Soriano, Simone; Aronico, Nicola; et al. (Frontiers in Medicine, 2024)
Diverticular disease (DD), commonly associated with elderly, is increasing among younger individuals. This retrospective study aimed to evaluate differences in the natural history and outcome between young and old patients with DD. Adult patients with DD diagnosed between 2010 and 2022 at an Italian tertiary referral centre were enrolled and demographic and clinical data were retrieved. Patients were categorised as young or old based on the 25th percentile of the population’s age at diagnosis. Univariate and multivariate analyses were fitted to assess the association of collected variables with the age of disease presentation. Additionally, survival analyses were conducted to evaluate the association between age of diagnosis and clinical outcomes at follow-up, namely disease recurrence, hospital access, surgery, and death. 220 DD patients (median age 66 years, IQR 55-74, F:M=1.4:1) were included, comprising 54 patients receiving a diagnosis before the age of 49 (young DD patients) and 166 diagnosed after (old DD patients). Young patients exhibited a significantly higher prevalence of male sex (57% vs 36%, p<0.01), smoking habit (38% vs 14%, p<0.01) and alcohol consumption (54% vs 38%, p=0.03). Complications at the time of diagnosis, particularly abscesses and free perforations, occurred more frequently in younger patients (p=0.04). Moreover, young DD patients experienced a higher rate of hospitalisation and surgical intervention (p=0.01 and p=0.04, respectively) over a median follow-up period of 5 years. Therefore, preventive strategies and prompt diagnosis are crucial in young patients with DD to assure better disease outcome and prevent complications.